Usability Evaluation and Solution Design Improvement of OCTO Friends as Banking Referral Application - Utami, Aisyah Nurlita; Santoso, Harry Budi (The Indonesian Journal of Computer Science, 2024)
OCTO Friends application was developed to allow customers to directly participate in banking product referral program, has not met expectations and targets. Only 10.6% of the 39,105 members actively provided referrals, and business conversion rate was only 10% of the target. This study aims to evaluate the application's usability and generate recommendations for interface design improvement. A mixed methods research approach was used, including quantitative research through user needs questionnaires and System Usability Scale (SUS), along with qualitative research through in-depth interviews and usability testing. Data collection through questionnaires involved 104 respondents, resulting in a list of user needs and SUS score of 66. The results showed that OCTO Friends is requires some improvements. In-depth interviews and usability testing for six main functions led to 46 interface design improvements, especially improvements in referral data input, follow-up referral, and incentive information functions as these are primary functions of referral application.